Self-assembled microfiber-like biohydrogel for ultrasensitive whole-cell electrochemical biosensing in microdroplets - Ma, Xiao-Meng; Wang, Jian-Wei; Zhao, Li-Ting; Zhang, Yafei; Liu, Jun-Ying; Wang, Songmei; Zhu, Daochen; Yang, Zhugen; Yong, Yang-Chun (American Chemical Society, 2023)
A novel microfiber-like biohydrogel was fabricated by a facile approach relying on electroactive bacteria-induced graphene oxide reduction and confined self-assembly in a capillary tube. The microfiber-like biohydrogel (d = ∼1 mm) embedded high-density living cells and activated efficient electron exchange between cells and the conductive graphene network. Further, a miniature whole-cell electrochemical biosensing system was developed and applied for fumarate detection under −0.6 V (vs Ag/AgCl) applied potential. Taking advantage of its small size, high local cell density, and excellent electron exchange, this microfiber-like biohydrogel-based sensing system reached a linear calibration curve (R2 = 0.999) ranging from 1 nM to 10 mM. The limit of detection obtained was 0.60 nM, which was over 1300 times lower than a traditional biosensor for fumarate detection in 0.2 μL microdroplets. This work opened a new dimension for miniature whole-cell electrochemical sensing system design, which provided the possibility for bioelectrochemical detection in small volumes or three-dimensional local detection at high spatial resolutions.